Strategi Pengelolaan Anggaran Produksi Berbasis Biaya Standar untuk Meningkatkan Profitabilitas UMKM Kerupuk Telur Asin - Dhyni Triyas Pitaloka; Lilik Dea Tantri; Unik Latifah; Arlita Umul Maffiroh; Muhammad Aditya Yulianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine how standard costing can be used as a tool for planning and controlling production costs in salted egg cracker micro, small, and medium enterprises (MSMEs). MSMEs need to manage their production costs effectively to increase their profitability in an era of increasingly fierce business competition. A case study was used to collect data through interviews, observations, and financial document analysis. The study shows that the implementation of standard costing has helped more accurate production cost budget planning. This makes it easier for management to compare standard costs with actual costs, which allows for effective and efficient cost control. Furthermore, the findings indicate that standard costing can serve as a benchmark and evaluation tool to improve operational effectiveness. Furthermore, this study suggests that MSMEs should incorporate a standard costing system into their financial reporting process and educate management and employees about the importance of cost control. Therefore, implementing standard costing can be a long-term strategy to keep the company operational and competitive in an increasingly competitive market.